Utilização da eletroforese em gel com gradiente de temperatura na determinação do perfil da microbiota cecal de frangos de corte contra Salmonella Enteritidis - Rodrigues, João Carlos Zamae [UNESP] (2015)
The intestinal microbiota of birds plays a fundamental role in the development of their production potential to ensure the proper functioning of a gastrointestinal tract and immune system closely linked to it. So many additives have been used to encourage the growth of a healthy microbiota, however, we still have no information about the desired profile for her. So we set out to use the Gel Electrophoresis with Temperature Gradient (TGGE) to assess the cecal microbiota of birds fed diets plus halquinol, caprylic acid and Lactobacillus, and subsequently challenged with Salmonella Enteritidis (SE). At 10, 20, 30 and 42 days old were quantified immunoglobulins IgA, IgM, IgY and interleukins 17:08 assessed cecal colonization IF (CFU / ml), cecal tonsil histopathological observation, and those related to resulatados cecal microbiota evaluated by TGGE method. The treatment with caprylic acid was equally effective in reducing the halquinol colonization by IF, followed by the group treated with Lactobacillus. IL-8 and IgM concentrations shown maturation and compared with the local and systemic immune development of the poultry, however, we do not identify relationship with the increased complexity of the microbiota between different trtamentos and challenged groups. In this study it was also not possible to reproduce the TGGE